PENGARUH MODEL LEARNING CYCLE 7E BERBANTUAN MEDIA VIRTUAL LAB DALAM MENINGKATKAN HASIL BELAJAR LISTRIK DINAMIS - AA Saputri; Stepanus Sahala Sitompul; Ray Cinthya Habellia (JURNAL EDUCATION AND DEVELOPMENT, 2024)
Physics is a subject that requires a high level of visualization and mastery of concepts in interpretation, so students find the subject difficult. Interpretation of physics material can be supported by the use of appropriate learning models and media in its implementation so that it affects the increased learning outcomes of students. This study examines how the effectiveness of the effect of the learning cycle 7E model assisted by virtual lab to make an increase in dynamic electricity learning outcomes. The design of this research design is One Grub Pretest-Posttest and Pre-Experimental Design method with the research sample, namely class IX B SMP Negeri 1 Sandai selected using random sampling technique. The assessment consists of 10 multiple choice questions. The research data showed that there were differences in dynamic electricity learning outcomes after the use of the learning cycle 7E model assisted by virtual lab media. This refers to the results of the Paired Sample T-Test which has a significance size of 0.000 <0.05; and the use of the learning cycle 7E model assisted by virtual lab is effective in learning, especially dynamic electricity learning. Judging from the effect size value obtained of 4.54 (classified as very high). Learning by using the learning cycle 7E model assisted by virtual lab media can be used as a comparison and can also provide a reference for teachers who face the problem of low cognitive learning outcomes of students.